2018
DOI: 10.3390/ijgi7030099
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Tourist Destinations and Comparative Analysis of Preferences Between Foreign Tourists and Domestic Tourists on the Basis of Geotagged Social Media Data

Abstract: Abstract:Inbound tourism plays an important role in local economies. To stimulate local economies, it is necessary to attract foreign tourists to various areas of a country. This research aims to develop a method of extracting the locations of tourist destinations in a country and to understand what characteristics foreign tourists expect of areas near tourist attractions compared with what domestic tourists expect. In this paper, a tourist destination is defined as a small area that has places of interests fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 36 publications
0
27
0
Order By: Relevance
“…Though there have been concerns regarding information bias and lack of standard quality control, several studies have empirically revealed that VGI is of equally good quality as authoritative data [8,28,29]. Several researchers have used VGI resources including geo-tagged contents (e.g., tweets and photos) [16][17][18]30], check-in data [18,30], OSM [31] and so on. VGI has been used in a variety of applications such as tourism studies [16][17][18]30], urban studies [19,25,32,33], land use and land cover detection [11,34] and mobility analysis [35].…”
Section: Volunteered Geographic Informationmentioning
confidence: 99%
See 3 more Smart Citations
“…Though there have been concerns regarding information bias and lack of standard quality control, several studies have empirically revealed that VGI is of equally good quality as authoritative data [8,28,29]. Several researchers have used VGI resources including geo-tagged contents (e.g., tweets and photos) [16][17][18]30], check-in data [18,30], OSM [31] and so on. VGI has been used in a variety of applications such as tourism studies [16][17][18]30], urban studies [19,25,32,33], land use and land cover detection [11,34] and mobility analysis [35].…”
Section: Volunteered Geographic Informationmentioning
confidence: 99%
“…Moreover, this proposed algorithm applied local maximum to extract attractive footprints to deal with the problem in dense areas. Maeda et al extracted the location of tourist destinations in Japan using geo-tagged tweets via attractiveness and originality of each place of interest [18]. Attractiveness was computed using DBSCAN clustering and gravity modeling.…”
Section: Extracting Interesting Regions From Vgimentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the Twitter and Foursquare data were also widely used in the travel behaviors analysis. For example, Maeda, T. et al [33,34] extracted the different preferences of tourists from different countries by characterizing each location. And Sun, Y. et al [35] empirically investigated the travel and activity patterns of active local Foursquare users in New York City.…”
Section: Travel Behaviorsmentioning
confidence: 99%